Implementation of Problem-Based Learning Model Assisted by Augmented Reality to Improve Learning Outcomes of MAN 2 Tidore Kepulauan Class XI Students on Newton’s Second Law - Asmita Basir; Nurdin Abdul Rahman; Mardia Hi Rahman (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of the application of the Problem Based Learning (PBL) model based on Augmented Reality (AR) on improving the learning outcomes of grade XI MAN 2 Tikep students on Newton's Law II material. The background of this research is based on the students' low understanding of the concept of force and motion material, especially the application of Newton's Law II in daily life. The research method used is a quasi-experimental design with a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class that received learning with the AR-based PBL model and the control class that used the PBL model with conventional media. Data was collected through learning outcome tests given before and after treatment (pretest and posttest). Data analysis was carried out using a t-test to find out the difference in learning outcomes between the two groups. The results showed that there was a significant difference between the learning outcomes of students in the experimental class and the control class. Students who participated in learning with the AR-based PBL model obtained higher scores on average compared to students in the control class. Thus, the application of the AR-based PBL model has proven to be effective in improving student learning outcomes in Newton's Law II material.